2020
DOI: 10.1002/aur.2435
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Functional Covariance Connectivity Between Gray and White Matter in Children With Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a type of neurodevelopmental disorder with atypical gray matter (GM) and white matter (WM) functional developmental course. However, the functional co‐developmental pattern between GM and WM in ASD is unclear. Here, we utilized a functional covariance connectivity method to explore the concordance pattern between GM and WM function in individuals with ASD. A multi‐center resting‐state fMRI dataset composed of 105 male children with ASD and 102 well‐matched healthy controls (HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…5a ; Supplementary Result 6 and Supplementary Table 2 ). The results were consistent with previous studies that reported functional abnormalities of WM in major depressive disorders 49 , schizophrenia 50 , 51 , and autism spectrum disorder 52 . The PLS1− ranking genes were also enriched for neurological diseases, including peripheral nervous system diseases, neurodegenerative disease, polyneuropathies, demyelinating diseases, hereditary motor and sensory neuropathies, muscle weakness, and neuromuscular diseases (all FDR-corrected P < 0.05; Fig.…”
Section: Resultssupporting
confidence: 93%
“…5a ; Supplementary Result 6 and Supplementary Table 2 ). The results were consistent with previous studies that reported functional abnormalities of WM in major depressive disorders 49 , schizophrenia 50 , 51 , and autism spectrum disorder 52 . The PLS1− ranking genes were also enriched for neurological diseases, including peripheral nervous system diseases, neurodegenerative disease, polyneuropathies, demyelinating diseases, hereditary motor and sensory neuropathies, muscle weakness, and neuromuscular diseases (all FDR-corrected P < 0.05; Fig.…”
Section: Resultssupporting
confidence: 93%
“…However, dual-peak patterns within the low-frequency range, as we reliably observed in DP voxels, have not been previously reported in GM. In addition, while recent studies have reported significant changes in the amplitude of low-frequency fluctuations (ALFF) in WM in patients with schizophrenia and autism spectrum disorder 33,34 , these findings were restricted to the intensity of Figure 9. The relationship between behavior scores and power spectral peaks in DP voxels across 199 subjects.…”
Section: Discussionmentioning
confidence: 83%
“…However, dual‐peak patterns within the low‐frequency range, as we reliably observed in DP voxels, have not been previously reported in GM. In addition, while recent studies have reported significant changes in the amplitude of low-frequency fluctuations (ALFF) in WM in patients with schizophrenia and autism spectrum disorder 33,34 , these findings were restricted to the intensity of spontaneous neural activity. The patterns of power spectra over the frequency range of interest correspond to variations in underlying HRF characteristics and may add insights to the functional mechanism underlying the association between signal features, neurovascular coupling, and anatomical substrates.…”
Section: Discussionmentioning
confidence: 96%
“…The product of the standard scores of each pair of voxels is the FCS. The FCS can be used to measure the strength of the functional covariance of each pair of voxels (Eisenberg et al, 2015;Chen et al, 2021).…”
Section: Calculating Functional Covariance Connection Strengthmentioning
confidence: 99%
“…Therefore, in this study we selected Parkinson's patients with hyposmia, and analyzed the differences between Parkinson's patients with hyposmia and normal subjects. The functional covariance connectivity (FCC) between the white and gray matter voxels was constructed based on ALFF maps (Chen et al, 2021) and explored its value as a potential neuroimaging marker for early diagnosis.…”
Section: Introductionmentioning
confidence: 99%